KLUB DETEKTIF BUKU: MENINGKATKAN MINAT BACA ANAK MELALUI PENDEKATAN KOMUNITAS BERBASIS MASYARAKAT - Hanni Pradana, Zein; Praja, Muhammad Panji Kusuma; Permatasari, Indah; Amrulloh, Abdul Fatah; Azzahra, Galuh Dwi; Dwisetyarini, Febrianti (Jurnal Abdi Insani, 2024)
The Klub Detektif Buku program aims to enhance children's reading interest in Karanggintung Village through a community-based approach that integrates literacy and technology. This program provides access to quality books through a mini library, interactive reading sessions, and book discussions. A total of 50 children, aged 6-12, as well as parents and the local community, actively participated in this program. The results showed an increase in reading interest in 64% of participants by 1 level, while the remaining 36% already had high reading interest from the beginning. The involvement of parents and the community proved to play an important role in the success of the program, creating an environment that supports children's literacy development. The use of technology also expanded children's access to quality reading materials. This program is expected to serve as a model that can be adopted by other regions facing similar literacy challenges.